Função atrial esquerda na estenose mitral reumática pela ecocardiografia tridimensional - Vinicius Tostes Carvalho (2013)
Introduction: Chronic rheumatic heart disease (CRC) is a public health problem in developing countries, an important cause of morbidity and mortality. Dilatation with dysfunction of the left atrium (LA) is a predisposing factor for the development of arrhythmias and thromboembolic events, clinical complication of the rheumatic mitral stenosis (MS). Therefore, knowledge of the factors associated with the function of LA in MS is of clinical importance as a substrate for atrial arrhythmias and onset of symptoms in these patients. Objectives: The aim of this study was to identify clinical and echocardiographic factors associated with LA emptying fraction in patients with MS. Methods: We evaluated 163 outpatients with rheumatic MS who were referral to the Hospital das Clinicas (HC) of UFMG and 20 normal controls. All subjects underwent clinical examination, electrocardiogram and two-dimensional (2D), and real-time three-dimensional (3D) echocardiography. The quantification of the MS severity, evaluation of the ventricles, pressure gradients and pulmonary arterial pressure were carried out in a conventional manner. LA function was assessed by LA emptying fraction (LAEF), expressed as a percentage change in volume from maximum to minimum. Results: Mean age was 42.7 ± 10.8 years with a predominance of females (85%). Most patients were in NYHA functional class I and II (83%) and only 27 (17 %) in functional class III or IV. Sixty-nine patients (43%) had undergone mitral valve intervention (surgical or percutaneous valvuloplasty) at enrollment into the study. Atrial fibrillation (AF) was detected by conventional 12-lead electrocardiogram in 31 patients (19%), nine of them with previous ischemic cerebral event. Mitral valve area was 1.24 ± 0.41 cm2, mean transmitral gradient was 9 ± 4.8 mmHg and systolic pulmonary artery pressure was 44 2 ± 14.4 mmHg. Overall LAEF was 30.1 ± 15.1%, different from controls (58.9 ± 6.7 p <0.001), with significant reductions in patients with AF compared to patients in sinus rhythm (19.9 ± 8.7% vs. 32.6 ± 15.3%, p <0.001). Measurements of the 3D LAEF had good inter-and intraobserver reproducibility (intraclass correlation coefficient of 0.935 and 0.878, respectively). Possible associations of clinical and echocardiographic variables with LAEF were tested by linear regression analysis, considering the dependent variable LAEF. Variables that remained in the multivariate model were the mitral valve area, the presence of AF, previous mitral valve intervention, mean gradient, and right ventricular function assessed by tissue Doppler. Conclusions: In patients with MS, the LA function is influenced by a combination of the echocardiographic parameters that express the duration of the disease and severity of the stenosis. LAEF assessment may be useful to identify patients at higher risk for developing AF and symptoms.